2006
DOI: 10.1051/0004-6361:20066043
|View full text |Cite
|
Sign up to set email alerts
|

A statistical analysis of X-ray variability in pre-main sequence objects of the Taurus molecular cloud

Abstract: Context. This work is part of a systematic X-ray survey of the Taurus star-forming complex with XMM-Newton. Aims. We study the time series of all X-ray sources associated with Taurus members, to statistically characterize their X-ray variability, and compare the results to those for pre-main sequence stars in the Orion Nebula Cluster and to expectations arising from a model where all the X-ray emission is the result of a large number of stochastically occurring flares. Methods. The analysis of the light curves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
111
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(126 citation statements)
references
References 32 publications
14
111
1
Order By: Relevance
“…Note that for the Sun, L X ≈ 2 × 10 27 erg s −1 and L bol ≈ 3.85 × 10 33 erg s −1 . Flaring is common in TTS (Stelzer et al 2007), the most energetic examples reaching temperatures of ≈ 10 8 K (Imanishi et al 2001).…”
Section: X-ray Driven Disk Chemistrymentioning
confidence: 99%
“…Note that for the Sun, L X ≈ 2 × 10 27 erg s −1 and L bol ≈ 3.85 × 10 33 erg s −1 . Flaring is common in TTS (Stelzer et al 2007), the most energetic examples reaching temperatures of ≈ 10 8 K (Imanishi et al 2001).…”
Section: X-ray Driven Disk Chemistrymentioning
confidence: 99%
“…Studies have used X-rays and extreme ultraviolet radiation to find α mostly in the range of 2-2.5 for G-M dwarfs (Audard et al 2000;Kashyap et al 2002;Güdel et al 2003) and for T Tauri stars (Stelzer et al 2007), supporting the view that moderate flares are the dominant heating source for these active coronae. This observation may indeed be the basis for the correlation between radio and soft X-ray emission in magnetically active stars and flares, the high level of apparently constant emission being the result of a large number of comparatively small flares not individually detected in the light curves (Telleschi et al 2005).…”
mentioning
confidence: 81%
“…Specifically, the rate of EUV flares above a given threshold scales linearly with the average X-ray luminosity of a late-type star (Audard et al 2000), a relation that was suggested to apply to T Tauri stars as well (Stelzer et al 2007).…”
mentioning
confidence: 99%
“…X-ray flares are also common in TTS, producing plasma temperatures of up to ≈10 8 K (Stelzer et al 2007;Imanishi et al 2001). Like in main-sequence stars, the flare peak temperature, T p , correlates with the peak emission measure, EM p (or, by implication, the peak X-ray luminosity), roughly as (Güdel 2004)…”
Section: Stellar X-ray Flaresmentioning
confidence: 99%